Виды рода Heteromurus Wankel, 1860 (Collembola, Entomobryidae, s. l.) в фауне СССР - Мартынова, Е.Ф.; Челноков, В.Г.; Расулова, 3.К. (Вестник зоологии, 1974)
The identification key and data on distribution in the USSR territory are presneted
for the species from the genus Heteromurus. The following two new species are described:
Heteromurus variabilis sp. n. from Tajikistan and Heteromurus caucasicus sp. n. from
Azerbaijan. The degree of variability in some characters significant for diagnostics of the
species is discussed.